Dynamics of Legal Certainty in Forest Area Management Between Economic Utilization and Environmental Sustainability - M. Arif Syahputra; Evita Isretno Israhadi (Majelis: Jurnal Hukum Indonesia, 2025)
This study explores the crucial role of legal certainty in the management of natural resources, with a focus on forest areas, as a key factor in ensuring a balanced approach to economic use, environmental sustainability, and the protection of community rights. Forests, both with and without tree cover, require clear legal frameworks to prevent overlapping claims, illegal activities, and degradation. The state's authority in regulating the status and function of forest areas is vital and must be supported by coherent, enforceable policies. Employing a normative juridical method, this research examines primary, secondary, and tertiary legal sources, particularly Law Number 41 of 1999 concerning Forestry, to assess the extent to which Indonesia’s legal system provides certainty in forest area governance. The findings reveal that legal certainty is still challenged by overlapping regulations, inconsistencies in enforcement, and gaps between formal legal provisions and their implementation in the field. These issues often lead to land conflicts, unclear tenure rights, and unsustainable exploitation. Nevertheless, when implemented effectively, the legal framework has the potential to promote responsible management practices, preserve biodiversity, and safeguard indigenous and local communities' rights. The study underscores the need for harmonizing sectoral laws, strengthening institutional coordination, and improving transparency in forest area designation and use. Legal certainty is not only a prerequisite for sustainable development but also a cornerstone for legal justice and equitable resource governance. This paper contributes to the discourse on forest policy reform and aims to inform legislators, policymakers, and stakeholders involved in natural resources management about the importance of strengthening legal foundations for better governance and sustainability.